2004
DOI: 10.1128/mcb.24.17.7469-7482.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor 4 Is Translationally Regulated by Hypoxic Stress

Abstract: Hypoxic stress results in a rapid and sustained inhibition of protein synthesis that is at least partially mediated by eukaryotic initiation factor 2␣ (eIF2␣) phosphorylation by the endoplasmic reticulum (ER) kinase PERK. Here we show through microarray analysis of polysome-bound RNA in aerobic and hypoxic HeLa cells that a subset of transcripts are preferentially translated during hypoxia, including activating transcription factor 4 (ATF4), an important mediator of the unfolded protein response. Changes in mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
347
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(365 citation statements)
references
References 61 publications
11
347
1
5
Order By: Relevance
“…Both expression and function of ATF4 have been reported to be regulated by the post-transcriptional pathways (Blais et al, 2004). Phosphorylation of the a subunit of translation initiation factor (eIF2a) promotes translation of ATF4 and ATF4 phosphorylated by RSK2 increases transactivation ability (Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Both expression and function of ATF4 have been reported to be regulated by the post-transcriptional pathways (Blais et al, 2004). Phosphorylation of the a subunit of translation initiation factor (eIF2a) promotes translation of ATF4 and ATF4 phosphorylated by RSK2 increases transactivation ability (Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…While salubrinal lowered caspase-3 activation to control levels, it was less effective in blocking nuclear pyknosis, Reports describing caspase-3-independent induction of EndoG activity by BNIP3 offer one potential explanation for this observation and reinforce the notion that combination therapies for stroke will likely be required (Zhang et al, 2007). It is possible that other non-ER kinases like PKR regulate eIF2α phosphorylation and neuron survival after hypoxic stress (Blais et al, 2004). Likewise, the physiologic stressors that activate PERK also activate the AMPK/TSC2/mTOR pathway (Liu et al, 2006).…”
Section: The Role Of Er-stress Signaling In Hypoxia-induced Apoptoticmentioning
confidence: 96%
“…What was most intriguing was the set of interactions uncovered among the bZIP transcription factors ATF4, CHOP-10, c-Jun and c/EBP-β. And while c-Jun, ATF4 and CHOP have been linked with cellular responses to hypoxia, c/EBP-β's role in hypoxic signaling has not been established (Blais et al, 2004;Ron and Habener, 1992). To investigate this further, we analyzed c-Jun and c/EBP-β expression by western blotting and found that hypoxia stimulated the transient induction of Jun and its downstream transcriptional target c/EBP-β before any appreciable induction of ATF4 was seen (Lin et al, 2002).…”
Section: Defining the Role Of Er-stress Responses In Hypoxia-induced mentioning
confidence: 99%
“…Figure 3a shows that the steady-state level of ATF3 mRNA increases under anoxia after 2 h and persists at 20 h. The increase in ATF3 mRNA level (Figure 3a) precedes the increase in ATF3 protein level (Figure 2a), suggesting that increased ATF3 protein accumulation in anoxia could be due to a later posttranscriptional event. We do not rule out other non-HIF-1 pathways of increased protein translation that could also contribute to ATF3 accumulation under anoxia (Blais et al, 2004). Figure 3b shows that the increase in ATF3 mRNA level under anoxia is independent of HIF-1a.…”
mentioning
confidence: 84%
“…Anoxia has been shown to regulate gene expression in an HIF-1-independent manner (Ameri et al, 2004;Blais et al, 2004). To investigate the extent and mechanisms of HIF-independent gene regulation under low oxygen tensions, we considered activating transcription factor 3 (ATF3), a member of the ATF/cAMP-responsive element binding protein family of transcription factors, as a potential master regulator to alter the cellular transcriptional programs under hypoxia and anoxia for the following reasons.…”
mentioning
confidence: 99%